The country-of-origin effect in the electronics industry : How Chinese-made products affect consumer perception - Salomäki, Tuuli (My University, 2025)
Country-of-origin (COO) is a central phenomenon in international business research, and one that affects consumer perceptions, consumer trust, as well as purchasing behavior. The globalized market complicates the COO-effect (COE), because the assigning of a COO is not as clear as before, due to globalized supply chains. Due to this, the importance of country-of-brand (COB) has risen, especially in consumers of developed countries. The thesis looks at COE from the point of view of Chinese electronics products in the B2C market. These parameters and the reviewing of recent events affecting China’s nation brand bring novelty to the subject. Factors influencing the phenomenon, such as consumer perception and consumer trust affecting China’s nation brand are reviewed through relevant studies and literature. Both domestic and foreign markets are looked at through a literature review, and China’s status as a developing country is highlighted as a factor in how it is seen as a manufacturer of complex electronics. It is found that China’s complex and dynamic nation brand and country image (CI) make a clear assessment of how China is seen as a COO in the sector difficult, and a shift in perceptions towards Chinese-made products is seen. Shifts in the geopolitical climate and China’s development have and will continue to shape the answer to the research question “How is China seen as a COO in the field of electronics?”. Generally, it is found that products of Chinese COBs are seen as less favourable, especially in developed markets. This is affected by concerns over quality, bootlegging, as well as data privacy. Chinese consumers have traditionally also had negative attitudes towards Chinese electronics, but there is a slight shift seen towards a more positive connotation.

Alkuperämaa (COO) on keskeinen ilmiö kansainvälisen liiketoiminnan tutkimuksessa, ja se vaikuttaa kuluttajien vaikutelmiin, luottamukseen, sekä ostokäyttäytymiseen. Globalisoituneet markkinat monimutkaistavat COO-efektiä (COE), sillä alkuperämaan määräytyminen ei ole yhtä suoraviivaista kansainvälistyneiden toimitusketjujen myötä. Samalla brändialkuperämaan (COB) tärkeys on korostunut, erityisesti kehittyneiden maiden kuluttajilla. Tutkielma tarkkailee COE:ta kiinalaisten elektroniikkatuotteiden perspektiivistä kuluttajamarkkinoilla. Nämä rajaavat parametrit, sekä ajankohtaisten tapahtumien vaikutusten arviointi Kiinan maabrändiin tuovat uutuutta COE tutkimukseen. Ilmiöön vaikuttavien komponenttien, kuten kuluttajavaikutelman ja kuluttajaluottamuksen merkitystä Kiinan maabrändiin tutkitaan relevanttien tutkimusten ja kirjallisuuden kautta. Sekä koti- että ulkomaisia markkinoita tarkastellaan kirjallisuuskatsauksen kautta, ja Kiinan asema kehittyvänä maana korostuu vaikuttajana Kiinan maakuvaan (CI) monimutkaisten elektroniikkatuotteiden saralla. Kiinan monimuotoinen ja dynaaminen maabrändi sekä CI vaikeuttavat selkeän arvion luomista siitä, kuinka Kiina havaitaan alkuperämaana sektorilla. Myös muutoksia kuluttajien asenteissa Kiinalaisvalmisteista elektroniikkaa kohtaan on nähtävissä. Muutokset geopoliittisessa ilmapiirissä ja Kiinan kehitystasossa ovat vaikuttaneet, ja tulevat jatkossakin vaikuttamaan siihen, mikä vastaus tutkimuskysymykseen ”Kuinka Kiina nähdään alkuperämaana elektroniikkatuotteiden sektorilla?” on. Yleisesti on huomattu, että kiinalaisbrändien tuotteet nähdään negatiivisemmin, ja niihin liittyy huolia esimerkiksi tuotteiden laadun, alkuperäisyyden ja tietosuojan suhteen. Nämä huolet ovat korostuneen vahvoja kehittyneillä markkinoilla. Myös kiinalaisilla kuluttajilla on perinteisesti ollut negatiivinen asenne kiinalaista elektroniikkaa kohtaan, mutta tässä on viimeaikoina näkynyt muutosta positiivisempaa kohti.
Keywords: Country-of-origin (COO), Country-of-origin effect (COE), Nation brand, Country image (CI) consumer perception, consumer trust, perceived quality, electronics, Alkuperämaa (COO), Alkuperämaa-efekti (COE), maabrändi, maakuva, kuluttajavaikutelma, kuluttajaluottamus, havaittu laatu, elektroniikka